Synthesis of eco-friendly nanofluids for enhancement of heat transfer and application in different flow configuration passages / Asif Khan - Asif, Khan (2020)
Since the invention of the heat exchangers, the working fluids such as water, ethyl glycol, oil and many others were used, however, they reveal relatively low thermal conductivity. Eco-friendly nanofluids and the cost-effective annular heat exchangers were introduced in this research to overcome the problem. In the present work, heat transfer coefficient and friction loss analyses of (TiO2 and GNP) water-based nanofluids were compared with DI-water flowing in annular conduit under turbulent flow regime. The nanoparticle weight concentrations of 0.1, 0.075, 0.05 and 0.025 wt.% were prepared by using a simple two-step method. The DI-water simulations were conducted by using ANSYS Fluent 18.2 (CFD commercial package) under steady turbulent flow conditions at high Reynolds number and constant heat flux boundary conditions with the varied inner flow passage configuration of the annular heat exchanger. The CFD analyses used the finite volume method, uniform surface heat flux boundary condition and SST-k-? model for the solver. The DI-water simulation demonstrated, the increase of the inner wall temperature in the square passage incomparison to the circular inner geometry. The experimental results exhibited the convective heat transfer coefficient enhancement with the increase of nanoparticles concentrations in the base fluid. The maximum Nusselt number and insignificant increment of friction factor resulted in the addition of nanoparticle into the base fluid. The remarkable enhancement of the heat transfer achievement were, 21.75% and 11.72% for the 0.1 wt.% of GNP-water and TiO2-water nanofluids over the base fluid in the turbulent flow regime. The results concluded that varying inner shape of the annular conduit and addition of nanoparticles enhances the rate of heat transfer and retards the energy consumption.